NEW CLINICAL TRENDS IN MODERN BIOCHEMISTRY (Literary review) - Khodzhieva Dilrabo Kamilzhonovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Modern biochemistry is a field of scientific research that reveals the secrets of living organisms and their functioning. One of the key areas in biochemistry is the study of the structure and function of proteins. Scientists are interested in amino acids and peptides, which are the main building blocks of proteins, and are also developing new methods for their synthesis and analysis. Enzymes are also an object of interest for biochemists. Research in this field is aimed at studying the mechanisms of catalysis and regulation of enzymatic reactions, which play an important role in the life processes of organisms.